Alkali base triggered intramolecular charge transfer metallogels based on symmetrical A–π–D-chiral-D–π–A type ligands. Issue 15 (14th March 2016) - Dixit, Manish Kumar; Pandey, Vinay Kumar; Dubey, Mrigendra
Abstract : Threel -tartaric acid based symmetrical chiral structural isomeric nitrobenzylidenes have been synthesized with intent to achieve isomer specific metallogels with intramolecular charge transfer properties. Notably, Na + afforded twisted fibre morphology whilst Li + gave merely long range fibres. Abstract : Threel -tartaric acid based symmetrical A–π–D-chiral-D–π–A type structural isomeric nitrobenzylidenes (1–3 ) have been synthesized with intent to achieve isomer specific metallogels with intramolecular charge transfer properties. Alkali metal ions in these systems not only trigger charge transfer but also play a vital role in gelation. The presence of intramolecular rather than intermolecular charge transfer as well as aggregation has been well established by various kinds of experiments using UV-vis, CD, 1 H NMR, DFT and crystallography techniques. The role of alkali metal ions in triggering ICT was proved by titration with their respective crown ethers. Notably, Na + afforded twisted fiber morphology whilst Li + gave merely long range fibers. The true gel phase material was proved by detailed rheological studies.